Pendekatan Pendidikan Pastoral Terhadap Krisis Identitas Remaja Gereja di Era Digital - Andre Shevcenco Mumu (PASOLO: Jurnal Ilmu Teologi dan Pendidikan Kristen, 2025)
The identity crisis among church teens in the digital age is reflected in the disparity between their behavior on social media and the Christian values taught in the church. This study aims to identify the underlying causes of this identity crisis and propose a pastoral education approach as a solution. Pastoral education integrates Christian Religious Education and Pastoral Counseling to provide a holistic approach that combines teaching and personal guidance. This qualitative descriptive study uses interviews and observations conducted in Toraget Village, Langowan Utara. The findings reveal that social media pressure, a lack of deep spiritual understanding, and insufficient personal guidance are the primary contributing factors. Proposed solutions include contextual teaching, group counseling, and collaboration between the church and parents. This research is expected to contribute to the development of relevant educational programs for church youth, helping them strengthen their identity as children of God in the digital age.